Iconography of The Passion of Christ in the Old Believer Tradition (with Reference to Manuscripts from Ural Book Depositories) - Anufrieva, Natalia V. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2020)
Research on Old Believer manuscript artefacts containing the apocryphal The Passion of Christ has allowed scholars to investigate the creation of text and images for this narrative. As a result of comparing and contrasting texts from Old Believer printed books and manuscripts (eighteenth to the early twentieth centuries), the foundational editions of this artefact are identified. The development of pictorial elements, such as the inclusion of new elements in individual images and entire compositions, is directly dependent on changes to the text. Borrowing from F. I. Buslaev’s comparative historical method for researching miniatures, the author analyses five manuscripts collected in Ural region. It provides the opportunity to define three sustained pictorial editions of the Passion cycle. The peculiarities and distinctions of these editions consist in the presence of certain standards in the positioning of figures and basic motifs within the miniatures. The considered manuscripts present different variants in the illuminated reproductions of the artefact: detailed text summaries that focus attention on elements of the narrative and the heterogeneity of the miniatures attached to them; the investigation of the iconographic tradition of Russian art and the copying of individual narratives from icons; and the unusual combination of folk art techniques with West European engraving samples (widely used in miniature art). The miniatures for the Passion cycle reflect three fundamental processes in the development of Russian art at the time: the maintenance of the canon of Old Russian painting, the influence of Western European art, and the ubiquitous presence and influence of decorative folk art on the artistic work of manuscript scribes.